Los enfoques vulgar, humanista y sistémico en el trabajo social y sus aportes en la intervención del trabajador social - Mirabá Feijoo, Ericsson Patricio (My University, 2021)
The intervention of the Social Worker in Social Work is translated as a fact that people, groups, the community and the social workers themselves have devised and developed. And given the few theories that support social work, it has based its professional development on theories of auxiliary sciences that allow it to act as an agent of change in its path of helping to improve the quality of life of human beings. The general objective of the research is to evaluate the contributions of the vulgar, humanistic and systemic approach used in the interventions of the Social Worker, and as specific objectives to identify the applicability and methodology used of the different approaches using an exploratory methodological design, with the purpose to analyze and interpret the phenomenon of study through previous inquiries of information gathered from different sources. It was concluded that the main contributions, applicability and methodologies used of the main approaches of Social Work are based on theories of other disciplines in order to apply them as tools for their intervention. In this way, its actions are based on other sciences, developing its intervention methodology using different methods, techniques, approaches and instruments. It is concluded that the vulgar approach is the basis of the immediate meaning between the individuals of the same culture, on the other hand, the humanistic approach as its object of study is to evaluate how man faces life, and the systemic approach focuses on explaining the principles of various phenomena about the organization.
La intervención del Trabajador Social en el Trabajo Social se traduce como un hecho que personas, grupos, comunidad y los mismos trabajadores sociales han ideado y desarrollado. Y dadas las escasas teorías que sustentan el trabajo social, este ha basado su desarrollo profesional en teorías de ciencias auxiliares que le permiten actuar como agente de cambio en su ruta de ayudar a mejorar la calidad de vida de los seres humanos. El objetivo general de la investigación es evaluar los aportes del enfoque vulgar, humanista y sistémico empleados en las intervenciones del Trabajador Social, y como objetivos específicos identificar la aplicabilidad y metodología empleada de los distintos enfoques utilizando un diseño metodológico de carácter exploratorio, con la finalidad de analizar e interpretar el fenómeno de estudio mediante indagaciones previas de información recabada de distintas fuentes. Se concluyó que los principales aportes, aplicabilidad y metodologías empleadas de los principales enfoques del Trabajo Social se basan en teorías de otras disciplinas con el fin de aplicarlos como herramientas para su intervención. De esta manera, su accionar se fundamenta de otras ciencias, desarrollando su metodología de intervención utilizando distintos métodos, técnicas, enfoques e instrumentos. Se concluye que el enfoque vulgar es la base del sentido inmediato entre los individuos de una misma cultura, en cambio, el enfoque humanista tiene como objeto de estudio evaluar cómo el hombre afronta la vida, y el enfoque sistémico se centra en explicar los principios de varios fenómenos sobre la organización.
Keywords: INTERVENCION; HUMANISTA; VULGAR; TRABAJO SOCIAL